(RE)TRAÇOS SOBRE A LEGENDAGEM DE OBRAS AUDIOVISUAIS NO/DO BRASIL. - Boito, Fernanda (Trabalhos em Lingüística Aplicada)
This article aims at contributing with research initiatives focusing on (re)tracing and discussing (hi)stories of subtitling of foreign films in Brazil and Brazilian films abroad. Methodologically, we carried out a literature review, including search in press archives, and critical discussion. The theoretical perspective adopted in this article is discursive-deconstructive. We highlight the importance of working on our epistemological legacies, particularly regarding Translation Studies, more specifically audiovisual translation. We also emphasize the need to begin thinking about subtitling more as a social-historical-discursive language practice and less as a mere 'bridge' of accessibility.